PENGARUH BENTUK LATIHAN DAN MOTIVASI BERPRESTASI TERHADAP KECEPATAN LARI ATLET SEPAKBOLA - Putra, Mu’arif Arhas (Edu Research, 2016)
This research begin from the speed problem of the Garuda Rokan Soccer School athlete. It’s so hard to pursuit the ball for the athlete, with lack of the speed ability athlete had a big problem to argued against the opponent team automatically.The purpose of this research is to know the influence of shadow drill exercise and sled towing speed cord towing and the achievement motivation toward speed of football athletes skill Garuda Rokan Soccer School. This research is quasi experiment. The population of this research comprises of all the Garuda Rokan Soccer School athlete, there are 140 athlete, divided into two group there are 27 % with high achievement motivation and 27% with low achievement motivation and 44 athlete as sample